ONLINE-BASED ENTREPRENEURSHIP LEARNING STRATEGIES IN GROWING ENTREPRENEURIAL ENTREPRENEUR PARTICIPANTS IN ELEMENTARY SCHOOL TEACHER EDUCATION UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - Situmorang, Harningsih Fitri (Hijri, 2024)
This study aims to provide students with independence in online entrepreneurship strategies so that the level of independence possessed by students continues to be instilled from an early age by utilizing various platforms available online. In this study using qualitative methods, namely research to describe and analyze phenomena, events, beliefs, attitudes, and social activities individually and in groups. Qualitative methods are a collection of methods for analyzing and understanding more deeply about the meaning of some individuals or groups considered as a humanitarian or social problem. The results of this study show that UMSU PGSD graduates in 2021 show 48.6% getting a job while 51.4% are not yet working. Therefore, PGSD students as the target group must be given attention and emphasis on increasing opportunities and entrepreneurship skills training programs